Pembelajaran Berdiferensiasi untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Bahasa Sunda - Sopy; Nunuy Nurjanah (Prodi Pendidikan Bahasa dan Sastra Daerah, 2024)
This research is a classroom action research that aims to increase the activity and learning outcomes of students. The subjects of this study were class VII students of SMPN 1 Pangandaran consisting of 32 students. Data collection techniques used instruments: (1) diagnostic assessment tests, (2) student activity observation sheets, and (4) learning achievement tests. Data were analyzed with descriptive statistical analysis and descriptive analysis. The results of this study indicate that: (1) the activity of students has increased, and (2) the average learning outcomes of Sundanese students are above the KKM score with a classical mastery level of 87.5%. From the results of this study it can be concluded that the application of a differentiated learning model can increase the activity and learning outcomes of students.